PERILAKU KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM MEMBENTUK KOMPETENSI PROFESIONALISME GURU - Kuni Azizah; Prim Masrokan; Binti Maunah (STAI Ma'had Aly Al-Hikam Malang, 2022)
AbstractBased on the problems that exist in the world of education, there is a need for the role of the principal as a supervisor to foster teachers to become professional educators. However, from within a teacher must also have a strong will to be more professional so that the goals of an education can be easily achieved. Professional teachers are not only required to master the material but the teacher can develop teaching materials, learning methods, can motivate students and have high insight in the world of education. Professional teachers cannot be separated from the role of a principal as a supervisor. A supervisor must be able to foster, provide direction and motivate teachers, this supervisor's behavior can shape the competence of teachers to become more professional teachers. The method used in writing this study uses library research or literature study by collecting data from books and journals related to supervisor behavior in shaping teacher professional competenceKeywords: Supervisor Behavior, Teacher Competence, Teacher Professionalism.AbstrakBerlatar belakang pada permasalahan yang ada dalam dunia pendidikan perlu adanya peranan kepala sekolah sebagai supervisor untuk membina para guru agar menjadi pendidik yang professional. Tapi, dari dalam diri seorang guru juga harus mempunyai kemauan keras untuk bisa lebih professional sehingga tujuan sebuah pendidikan bisa mudah untuk dicapai. Guru professional tidak hanya dituntut untuk menguasai materi tetapi guru itu bisa mengembangkan bahan ajar, metode pembelajaran, bisa memotivasi peserta didik dan memiliki wawasan yang tinggi dalam dunia pendidikan. Guru yang profesioal tidak terlepas dari peranan seorang kepala sekolah sebagai supervisor. Seorang supervisor harus bisa membina, memberikan arahan dan memotivasi para guru, perilaku supervisor ini yang dapat membentuk kompetensi guru menjadi guru yang lebih professional. Metode yang digunakan dalam penulisan penelitian ini menggunakan penelitian kepustakaan atau studi literature dengan mengumpulkan data dari buku-buku dan jurnal-jurnal yang berkaitan dengan perilaku supervisor dalam membentuk kompetensi profesionalisme guru.Kata Kunci: Perilaku Supervisor, Kompetensi guru, Profesionalisme guru